Influence of Ingestion of Eicosapentaenoic Acid-Rich Fish Oil on Oxidative Stress at the Menstrual Phase: A Randomized, Double-Blind, Placebo-Controlled, Parallel-Group Trial - Yoshihiko Mano; Ayaka Kato; Nobuo Fukuda; Keiko Yamada; Kenichi Yanagimoto (Mary Ann Liebert, 2022)
Background: This study examines the effect of the supplements on the redox reaction in menstrual cycle. Participants took eicosapentaenoic acid (EPA)-rich fish oil supplements over two menstrual cycles. Materials and Methods: For this randomized, double-blind, placebo-controlled trial, 21 female members of a university basketball team were selected. Participants were allocated into the EPA/docosahexaenoic acid (DHA) group (EG, n?=?11) and control group (CG, n?=?10) through stratified randomization. The EG and CG took 3600?mg fish oil (containing 900?mg EPA and 403?mg DHA) and 3600?mg corn oil (without EPA and DHA), respectively, every day for two menstrual cycles. The redox reaction was measured four times: the menstrual and follicular phases in two menstrual cycles. Results: There was a significant difference in reactive oxygen metabolites (d-ROMs) and potential antioxidant capacity during the menstrual phase by the main effect of time (before and after intake) in EG and CG (p?<?0.01). In a subsequent test, d-ROMs were significantly lower after intake in EG and CG (p?<?0.05); however, no significant difference in potential antioxidant capacity was found. A significant difference was noted in d-ROMs and potential antioxidant capacity during the follicular phase by the effect of time (before and after intake) only in EG (p?<?0.01). Significant decreases in d-ROMs and increases in potential antioxidant capacities were observed after intake (p?<?0.05). Conclusion: EPA-rich fish oil supplementation over two menstrual cycles demonstrated active involvement in the antioxidant function during menstrual and follicular phases. The protocol was registered at the University Hospital Medical Information Network Clinical Trial Registry (registration no. UMIN000028795).